A Correlational Study on Reading Interest and Reading Motivation of the Secondary School Students - Devina J Alodia (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2024)
Reading is fundamental to understanding and taking inspiration from texts. Students' reading interests can influence their reading motivation. They will be more motivated to read if they are interested in reading. Someone who has a strong interest in reading, as well as clarity and enjoyment in carrying out reading activities, is assumed to be motivated in reading and can instruct himself to read. A correlational research design was used in this research. This research aims to find out whether there is a relationship between reading interest and reading motivation in class XI students. This research sample was selected using convenience sampling techniques. Data collection was carried out using reading interest and reading motivation questionnaires. The relationship between reading motivation and reading interest was tested and applied to find correlations using the non-parametric Spearman rank correlation statistical test. From the results of the data analysis, it was found that students' interest in reading did not correlate significantly with reading motivation which means that it shows that students' interest in reading does not affect their reading motivation.